EVALUATION OF BIOACTIVE COMPOUNDS, IN-VITRO ANTIOXIDANT PROFILE AND ANTI-INFLAMMATORY PROPERTIES OF ETHANOLIC EXTRACTS OF ISOBERLINIA TOMENTOSA - Adekilekun, Ajibola Habeebulahi; Omodamiro, Olorunshola Dave; Achi, Ngozi Kalu; Oyewusi, Habeebat Adekilekun; Omodamiro, Rachel Majekodunmi; Tijani, Bashar Adekilekun; Oladipo, Oluwatosin Olubunmi; Oyeyemi, Bolaji Fatai (FUDMA Journal of Sciences, 2025)
Oxidative stress and chronic inflammation are interlinked pathological processes implicated in the onset and progression of various chronic diseases. Isoberlinia tomentosa, a Fabaceae family species traditionally used in African medicine, has limited scientific validation despite its ethnomedicinal relevance. This study evaluated the phytochemical composition, in-vitro antioxidant profile, and in-vivo anti-inflammatory activity of the ethanolic fruit extract of I. tomentosa. Qualitative screening revealed significant levels of phenolic compounds, tannins, saponins, terpenoids, and alkaloids. Quantitative GC-FID analysis identified 22 bioactive compounds, including catechin, quercetin, kaempferol, rutin, and apigenin. Acute toxicity testing in Wistar rats indicated an LD₅₀ greater than 5000 mg/kg, suggesting a favorable safety profile. Antioxidant assays (DPPH, ABTS, H₂O₂, OH•, NO• scavenging, FRAP, and TAC) demonstrated strong, dose-dependent radical-scavenging and reducing activities. In an oval albumin-induced paw edema model, the extract significantly reduced inflammation in a dose-dependent manner, with the 1000 mg/kg dose outperforming indomethacin (p < 0.05). These findings provide scientific evidence for the traditional use of I. tomentosa, highlighting its potent antioxidant and anti-inflammatory activities, high safety margin, and potential as a source of plant-based therapeutics for oxidative stress- and inflammation-related disorders.
Keywords: Anti-inflammatory; Antioxidant; GC-FID; Isoberlinia tomentosa; Oxidative stress; Phytochemicals